2006
DOI: 10.1094/phyto-96-1060
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Photosynthesis in Grapevines Affected by Esca

Abstract: To further understand the development of esca disease in grapevine, its physiological impact on plants grown in the vineyard was characterized, focusing mainly on photosynthesis. For this purpose, the state of the photosynthetic apparatus was evaluated in symptomatic and asymptomatic leaves in esca-infected grape plants, and wood carbohydrates stored in annual canes were assayed. In symptomatic leaves, esca greatly affected grapevine physiology. Foliar symptoms were associated with both stomatal closure and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 43 publications
(53 reference statements)
5
64
2
3
Order By: Relevance
“…Similar effects were reported by Petit et al (2006). These results suggest that esca foliar symptoms do not seem to be due to water stress.…”
Section: Comparison Between Healthy and Symptomatic Leaves Belonging supporting
confidence: 87%
See 1 more Smart Citation
“…Similar effects were reported by Petit et al (2006). These results suggest that esca foliar symptoms do not seem to be due to water stress.…”
Section: Comparison Between Healthy and Symptomatic Leaves Belonging supporting
confidence: 87%
“…As yet there is no effective treatment and the use of the only chemical treatment (sodium arsenite) has been forbidden. Thus, characterising the impact of esca on grapevine physiology represents a key step in pointing out a target that could enable control of this disease (Petit et al, 2006).…”
mentioning
confidence: 99%
“…Foliar symptoms were associated with stomatal closure and alteration of the photosynthetic apparatus. A decrease in CO 2 assimilation, transpiration, a significant increase in intercellular CO 2 concentration, a strong drop in the maximum fluorescence yield and the effective Photosystem II quantum yields, and a reduction of total chlorophyll but a stable carotenoid content were reported (Petit et al, 2006).…”
Section: Photosynthesis and Pathogens Invasions 231 Photosynthesis mentioning
confidence: 98%
“…It is suggested that plants switch off photosynthesis and other assimilatory metabolism to initiate respiration and other processes required for defence (Berger et al, 2007). Recently, Petit et al (Petit et al, 2006) characterized the photosynthetic apparatus of grape leaves infected with esca disease. Foliar symptoms were associated with stomatal closure and alteration of the photosynthetic apparatus.…”
Section: Photosynthesis and Pathogens Invasions 231 Photosynthesis mentioning
confidence: 99%
“…EVects of fungicides on photosynthesis have been already revealed by modiWcations of photosynthetic activity, chlorophyll Xuorescence, pigment contents or thylakoid function and integrity (Van Iersel and Bugbee 1996;Benton and Cobb 1997;Saladin et al 2003b;Alaoui-Sossé et al 2004;Xia et al 2006). An alteration of photosynthesis may disturb the whole carbon balance of the plant aVecting both restitution of reserves to storage organs (Petit et al 2006) and carbon nutrition in annual leaves and inXorescences (Saladin et al 2003a, b;Lebon et al 2005).…”
Section: Introductionmentioning
confidence: 99%